2015
DOI: 10.1016/j.combustflame.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of turbulent lifted methane jet flames: Effects of air-dilution and transient flame propagation

Abstract: Turbulent lifted methane jet flames with various air-dilution levels and a range of inlet velocities are simulated. A partially premixed combustion model based on premixed flamelets with presumed joint Probability Density Function (PDF) is used. The joint PDF is obtained using a copula to include the statistical correlation between mixture fraction, Z, and progress variable, c. The non-premixed combustion effect is included using a simple algebraic model. Both steady and unsteady RANS simulations are performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 67 publications
8
82
0
Order By: Relevance
“…All the flames considered are located on a cylindrical pipe, discharging pure fuel vertically, in the absence of any pilot flame. The presence of cross winds [1] can reduce combustion efficiency, as can the presence of inert gas, such as nitrogen and carbon dioxide [2], as well as air [3,4]. A review of the extensive experimental data on jet flame heights and lift-off distances is presented in [5].…”
Section: Introductionmentioning
confidence: 99%
“…All the flames considered are located on a cylindrical pipe, discharging pure fuel vertically, in the absence of any pilot flame. The presence of cross winds [1] can reduce combustion efficiency, as can the presence of inert gas, such as nitrogen and carbon dioxide [2], as well as air [3,4]. A review of the extensive experimental data on jet flame heights and lift-off distances is presented in [5].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the two additional residual terms involving cross correlation between the temporal and spatial averaging procedures [10] are considered to be negligible for this study as in [11]. Previous RANS studies [7,8,12,13] showed that the total time-averaged correlation, {Z c }, is quite influential in partially premixed lifted flames. This was further confirmed in a recent experimental study by Barlow et al [5] showing a strong Z-c correlation in a partially premixed piloted jet flame.…”
Section: Introductionmentioning
confidence: 99%
“…In the Reynolds-averaged Navier-Stokes (RANS) context, the effect of this correlation has been assessed previously by Ruan et al [7] and Chen et al [8] using a presumed joint probability density function (JPDF) approach for turbulent lifted flames. The statistical correlation was included in the JPDF using a copula method [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the prediction of blow-off, as the ultimate limiting condition of lift-off, when localised extinctions cause the flame to simultaneously leave the burner and extinguish, presents more severe modelling problems [5]. They include the development of oscillatory, non-linear phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…There have been significant successes in the mathematical modelling of lift-off distances, L, and plume heights for pure fuel jet flames, and in the associated formulation of appropriate dimensionless groups for the correlation of experimental data [2][3][4][5][6]. The region between the exit plane of a fuel jet discharging into the atmosphere and the flame leading edge is one of intense mixing that generates high strain rates.…”
Section: Introductionmentioning
confidence: 99%